Social security programs and retirement around the world working longer - Coile, Courtney; Milligan, Kevin; Wise, David A. (National Bureau of Economic Research conference report., 2019)
"This volume draws from the International Social Security project, which commenced more than two decades ago and which compares the social security and retirement experience in twelve developed countries. Both men and women are remaining longer in the workforce and this volume documents trends and considers the factors that contribute to this extension of work lives. This work evaluates the impact of factors such as improving health and education, changes in the occupation mix, the retirement incentives of social security programs, and the emergence of women in the workplace. The editors and contributors conclude that social security reforms as well as other factors such as the movement of women into the labor force have likely place an important role in this shift"--